Perlindungan Hukum Bagi Korban Salah Tangkap Dalam Konteks Hukum Acara Pidana - Khoiru Ummah, Padillah Kuntum; Lasmadi, Sahuri; Najemi, Andi (Faculty of Law, Universitas Jambi, 2025)
This research is conducted with theaim of analyzing how the rules and forms of legal protection for wrongful arrest victims are viewed from the context of criminal procedural law. The occurrence of wrongful arrest is an act that greatly harms the victim and violates Human Rights. Of course, as a result of this wrongful arrest, the victim suffers many material and immaterial losses. Using the normative juridical research method, this study examines the legal provisions regarding the rules of legal protection for victims of wrongful arrest. Legal protection for victims of wrongful arrest has been regulated in the Criminal Procedure Code (KUHAP) and how the protection is provided to victims of wrongful arrest. In this case, the rules for protecting victims of wrongful arrest have actually been regulated in Law Number 8 of 1981, which states that victims of wrongful arrest are entitled to compensation and rehabilitation due to procedural errors in the arrest. Furthermore, the issue of compensation is regulated in Government Regulation Number 92 of 2015, which stipulates that compensation should be provided within 14 days after it is submitted. However, in the provision of compensation, there are still several matters that require more attention and oversight, namely the deadline for providing compensation, which should be given within 14 days after the compensation claim is submitted. This is evidenced by the fact that many wrongfully arrested victims do not receive compensation within the time frame stipulated in the regulations. Therefore, there is a need for reaffirmation and renewed attention to this regulation because there is no certainty about the sanctions that can be imposed on officials who provide compensation if it is given more than 14 days later. Abstrak Penelitian ini berfokus pada bagaimana undang-undang dan metode perlindungan hukum bagi korban salah tangkap dipandang dari sudut pandang hukum acara pidana. Salah tangkap adalah tindakan yang merugikan korban dan melanggar Hak Asasi Manusia. Korban mengalami banyak kerugian material dan immaterial sebagai akibat dari tindakan salah tangkap ini. Penelitian ini menyelidiki ketentuan hukum mengenai bentuk perlindungan hukum bagi korban salah tangkap dengan menggunakan pendekatan penelitian yuridis normatif. Hukum KUHAP mengatur perlindungan korban salah tangkap dengan menyediakan ganti kerugian dan rehabilitasi. Namun, ganti kerugian memerlukan perhatian dan pengawasan tambahan. Salah satunya adalah tenggat waktu pemberian ganti kerugian, yang harus diberikan selama 14 hari setelah diajukannya.